TINJAUAN PELAKSANAAN SISTEM PENDAFTARAN ONLINE RAWAT JALAN DI PUSKESMAS KABUPATEN SEMARANG - Nugraheni Kusumawati; Sylvia Anjani; Haiqal Faqih; Widya Ratna Wulan (Jurnal Kesehatan, 2025)
Manual outpatient registration often leads to long queues, especially during the first 105 minutes after the service opens, causing patients to experience waiting times that exceed the standard (±8.8 minutes per patient compared to the 5–7-minute standard). Puskesmas Lerep has provided an online registration service through the Mobile JKN application since 2024. However, the utilization of this online service remains suboptimal, as most patients continue to register manually, and registration waiting times are still above the minimum service standard. This study aims to analyze the implementation of the online registration system for outpatient services using the 5M approach (Man, Material, Method, Machine, and Money). A descriptive qualitative method was employed. Data were collected through interviews and observations conducted at Puskesmas Lerep, Semarang Regency, in August 2025. The results indicate that the technical implementation of the online registration system is functioning well and there are no complaints regarding the system’s interface. However, elderly patients are unable to operate the Mobile JKN application, leading them to prefer registering directly at the puskesmas. The Man aspect worked adequately as staff could operate the system well and maintain smooth inter-unit communication. The Material aspect was considered sufficient, although small technical issues such as manual data updates remained. The Method aspect was consistently applied according to regulations. The Machine aspect functioned stably with minimal problems such as occasional internet connection disruptions. Meanwhile, the Money aspect still depended on funding submissions to the Health Office. Overall, the online registration system at Lerep Primary Healthcare improved service efficiency but required enhancements in outreach and equipment maintenance. Keywords: online registration; 5M approach; implementation review; outpatient; SIMPUS